Ultrasonic Echosignal Applied to Human Skin Lesions Characterization - PIOTRZKOWSKA, Hanna; LITNIEWSKI, Jerzy; SZYMAŃSKA, Elżbieta; NOWICKI, Andrzej (Archives of Acoustics, 2012)
The paper presents a classification of the healthy skin and the skin lesions (basal cell carcinoma) basingon a statistics of the envelope of ultrasonic echoes. The echoes envelopes distributions were modeled usingRayleigh and K-distribution. The distributions were compared with empirical data to find which of thembetter models the statistics of the echo-signal obtained from the human skin. The results indicated thatthe K-distribution provides a better fit.Also, a characteristic parameter of the K-distribution, the effective number of scatterers (M), wasinvestigated. The values of the M parameter, obtained for the skin cancer (basal cell carcinoma), werelower as compared to those obtained for the healthy skin. The results indicate that the statistical quan-titative ultrasound parameters have a potential for extracting information useful for characterization ofthe skin condition.